Penerapan Rencana Pelaksanaan Pembelajaran TIK dalam E-Learning menggunakan Aplikasi Moodle - Ngatiman, Ngatiman; Hendradi, Purwono; Agung Prabowo, Nugroho (Universitas Muhammadiyah Magelang, 2019)
E-learning is one of the most popular learning media at this time, by using e-learning education is expected not to span distance and time, so that education can be impressed anytime anywhere using the internet. After conducting research, the authors chose moodle as an e-learning application that will be used because moodle has many advantages both in managing questions to the level of user authentication coupled with good data security. By using moodle, the correction process that used to take a lot of time now is no longer. Even more practical and easier. The author in conducting research using the method of observation, research, analysis, planning, design, testing or testing and implementation It is hoped that the learning that has been created can continue to be used to support learning in SMP Negeri 2 Gombong. The results of the research are Moodle-based e-learning. This learning has been applied in SMP Negeri 2 Gombong, Kebumen Regency. Functionality testing has also been carried out by Admin, Teachers and Students. The results of tests carried out, in terms of logins, user management, question management, features to logout have all been said to be successful. This e-learning learning system can have a good impact on improving the quality of education in SMP Negeri 2 Gombong.